Antibacterial Activity of Amfoang Wild Honey Enriched with Red Ginger (Zingiber officinale var rubrum) Extract against Escherichia coli - Rohi Bire, Winioliski L.O.; Pollo, Resky Alexander; W. Djuma, Agustinda (LPPM Universitas Dhyana Pura, 2025)
Escherichia coli is a Gam-negative, short rod-shaped, non-spore-forming bacterium that normally inhabits the human intestine. However, when its population exceeds the normal limit or when it relocates from its natural habitat (the large intestine) to other parts of the body, it can pose a serious health risk. Numerous reports have indicated increasing antibiotic resistance in E. coli, which has encouraged the use of natural products for disease prevention and treatment. Honey and red ginger (Zingiber officinale var. rubrum) are among the natural ingredients known to contain antibacterial compounds such as polyphenols, flavonoids, glycosides, and phenolic derivatives including gingerol and shogaol. This study aimed to determine the inhibitory activity of Amfoang honey enriched with red ginger extract (Zingiber officinale var. rubrum) against the growth of Escherichia coli. Red ginger extracts at concentrations of 25%, 50%, 75%, and 100% were mixed with wild honey in a 1:1 ratio. Antibacterial testing was conducted using the disc diffusion method. Amoxicillin 30 µg served as the positive control, while a blank disc soaked in sterile distilled water was used as the negative control. After 24 hours of incubation, inhibition zone diameters were recorded as 24.1 mm, 25.0 mm, 24.0 mm, and 15.8 mm for concentrations of 25%, 50%, 75%, and 100%, respectively. These results indicate that the 50% concentration produced the geatest antibacterial activity, with an inhibition zone of 25.0 mm.